ECO-MIND: enhancing pro-environmental behaviours and mental health through nature contact for urban youth : a research protocol for a multi-country study using geographic ecological momentary assessment and mental models - Bubalo, Martina; Van den Broek, Karlijn; Helbich, Marco; Labib, S. M. (BMJ open, 2024)
Introduction Urban youth are experiencing increasing mental health problems due to diverse personal, social and environmental concerns. Youths’ detachment from natural environments, including green and blue spaces, may intensify such issues further. Contact with nature can benefit mental health and promote pro-environmental behaviour (PEB). Yet, only a few studies assess these relationships among the youth usually ignoring effects of living in diverse urban contexts, and everyday nature experiences. ECO-MIND will investigate whether urban youth’s dynamic greenspace exposure and their mental models about nature connectedness explain the associations between greenspace exposure, mental health and PEB in multiple urban contexts. - Methods and analysis We will collect data from university students from the Global South (ie, Dhaka, Kampala) and Global North cities (ie, Utrecht). Participants aged 18-24 will be recruited through stratified random sampling. We will use geographic ecological momentary assessment to assess respondents’ everyday experiences and exposure to greenspaces. Our definition of greenspace exposure will be based on the availability, accessibility and visibility of greenspaces extracted from satellite and street view images. We will administer a baseline questionnaire to participants about mental health, nature connectedness and PEB characteristics. Further, we will ask participants to build mental models to show their perception of nature connectedness. Finally, we will fit partial least square structural equation models and multi-level models to our longitudinal geographic momentary assessment data. - Ethics and dissemination The study was approved by the Ethical Review Board of the Utrecht University (Geo S-23221). Informed consent must be given freely, without coercion and based on a clear understanding of the participation in the study. Findings will be disseminated in peer-reviewed journals and at conferences. Furthermore, we will implement public engagement activities (eg, panel discussion) to share results among local stakeholders and policymakers and cocreate policy briefs.
Gesehen am 07.04.2025